IMPLEMENTASI DESAIN GRAFIS DALAM PEMBELAJARAN ILMU FALAK (STUDI KASUS PRODI ILMU FALAK UIN ALAUDDIN MAKASSAR - Basiri, Suandi; Wakia, Nurul (HISABUNA: Jurnal Ilmu Falak, 2024)
Abstract The article discusses the Implementation of Graphic Design in Learning Falak Science (Case Study of Falak Science Study Program UIN Alauddin Makassar). The main formulation of this research problem is further elaborated into two namely: First, How is the concept of Falak Science graphic design in the digital era? Second, How is the implementation of graphic design on the development of Falak Science? This type of research is field research, which is a method that describes and analyzes the results of research based on facts found in the field. Then this type of research can also provide more specific and accurate data on the object of research. Where, the object in this study refers to the Graphic Design Implementation in Falak Science Learning in the Falak Science Study Program at UIN Alauddin Makassar. The results of this study indicate that the response of students majoring in Falak Science at UIN Alauddin Makassar thinks that graphic design in learning falak science has been proven to increase students' understanding of the material taught so that it makes it easier for students to get information more effectively and efficiently about Falak Science. Graphic design also has a positive impact on students' technological skills. Students become more accustomed and skilled in using various graphic design software that is useful not only in the context of Falak Science learning as in the use of Falak Science applications. The implication of this research is that research can develop Falak Science learning modules that make maximum use of graphic design, so that the material can be delivered in a more interesting and easy-to-understand way. Further research on the long-term impact of using graphic design in learning and evaluating its effectiveness in various other courses.